FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2007 – 2010 (Students' Journal of Accounting and Banking, 2012)
Dividend policy is the amount of revenue that will be provided to investors. The purpose of this study was to examine and analyze the influence of cash ratio, debt to equity ratio (DER), return on assets (ROA) and earnings per share (EPS) on dividend policy.Based on the selection criteria in this study found 22 companies, resulting in pooling of data 88. Analytical methods used to analyze the influence of cash ratio, debt to equity ratio (DER), return on assets (ROA) and earnings per share (EPS) of the dividend policy is a multiple linear regression analysis.The results of this study can be concluded that: (1) Cash ratio is a positive influence on dividend payout ratio is acceptable, meaning that the higher the cash ratio will increase the dividend payout ratio. (2) Debt equity ratio negatively affect the dividend payout ratio is rejected, meaning that the debt equity ratio does not affect the dividend payout ratio. (3) Return on assets has a positive effect on dividend payout ratio means the higher the acceptable return on assets will increase the dividend payout ratio. (4) Earning per share has a positive effect on dividend payout ratio is acceptable, meaning that the higher the earnings per share would increase the dividend payout ratio.This study is limited to empirical studies of factors - factors that affect dividend policy of manufacturing companies went public on the Stock Exchange but is not up to solving the problem of how the impact of dividend policy on the performance of the company itself. Therefore, other researchers interested in the problems of the manufacturing company's capital structure to develop this research in order to determine the impact of dividend policy that used the company to company performance. For the study hereinafter may add other variables outside the model study, for example, inflation.Keywords: cash ratio, debt to equity ratio (DER), return on assets (ROA), earnings per share (EPS) and dividend policy